2008 13th International Power Electronics and Motion Control Conference 2008
DOI: 10.1109/epepemc.2008.4635632
|View full text |Cite
|
Sign up to set email alerts
|

SiC power semiconductor devices for new applications in power electronics

Abstract: This paper addresses the benefits of SiC semiconductor, owning excellent physical properties able to fulfill new scope of applications in terms of high temperature, high voltage and for more specific applications. Devices and applications developed at Ampere laboratory are detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, the on-resistance ranges shown in [22], i.e. 2.7 mΩ·cm 2 to 55 mΩ·cm 2 , are still considerably higher than the theoretical limit of 1 mΩ·cm 2 [24], due to the low channel mobility caused by poor SiO 2 /SiC interface quality [27]. One approach to further lower on-resistance uses an Implantation and Epitaxial MOSFET (IEMOSFET) as developed in [28] that achieves a 1.8 mΩ·cm 2 on-resistance.…”
Section: Use Of Wide-bandgap Semiconductormentioning
confidence: 97%
See 1 more Smart Citation
“…However, the on-resistance ranges shown in [22], i.e. 2.7 mΩ·cm 2 to 55 mΩ·cm 2 , are still considerably higher than the theoretical limit of 1 mΩ·cm 2 [24], due to the low channel mobility caused by poor SiO 2 /SiC interface quality [27]. One approach to further lower on-resistance uses an Implantation and Epitaxial MOSFET (IEMOSFET) as developed in [28] that achieves a 1.8 mΩ·cm 2 on-resistance.…”
Section: Use Of Wide-bandgap Semiconductormentioning
confidence: 97%
“…For the same breakdown voltage, devices made from 2H-GaN have the lowest theoretical on-state resistance, followed by 4H-SiC, 6H-SiC, and 3C-SiC [24]. Among those 4H-SiC is the most promising material due to its quality of crystal growth, maturity of manufacturing process and material characteristics [25].…”
Section: Use Of Wide-bandgap Semiconductormentioning
confidence: 98%
“…Nowadays, the technological advances in the power electronics field, allows the voltage levels in HVDC networks to be adjusted. Indeed, recent researches showed that Silicon Carbide (SiC) semiconductors can operate at higher voltages than Silicon (Si) semiconductors [2].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make them suitable as etch masking layers during advanced semiconductor, solar cell and micro-electro mechanical system (MEMS) fabrication. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Examples of these applications include deep etching of glass or silicon, protection of low-K dielectric films, as a stop layer in STI CMP, etc. 10,12,14 The planar surface necessary to use a-SiC as a hard mask in these applications can be potentially achieved using chemical mechanical planarization (CMP).…”
mentioning
confidence: 99%